2012
DOI: 10.1111/j.1748-0361.2012.00422.x
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Syndrome: Are Rural Residents at Increased Risk?

Abstract: Rural dwelling was associated with higher prevalence of metabolic syndrome among adults in the Unites States, which can be attributed to the differences in demographic composition and obesity-related behavioral factors between urban and rural residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 38 publications
4
51
3
Order By: Relevance
“…The high prevalence of MS in our study could be related with high prevalence of obesity, diabetes, dyslipidemia and hypertension due to changes of lifestyles and food intakes in China2627. In consistent with most of these previous studies2425, we found that the MS incidence was more common in female (45.0% and 23.7% in 2013 and 2007-2008, respectively) than in male (that is 39.8 and 17.5%) in rural areas of East China.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The high prevalence of MS in our study could be related with high prevalence of obesity, diabetes, dyslipidemia and hypertension due to changes of lifestyles and food intakes in China2627. In consistent with most of these previous studies2425, we found that the MS incidence was more common in female (45.0% and 23.7% in 2013 and 2007-2008, respectively) than in male (that is 39.8 and 17.5%) in rural areas of East China.…”
Section: Discussionsupporting
confidence: 90%
“…However, our data is lower than that in rural Handan of China in 2006–2007 in which the prevalence of MS was 39.7% and 54.2% in men and women respectively24. The MS prevalence was increased rapidly and it was 42.6% in East China in 2013, which is comparable with some developed countries or areas, such as rural USA (39.9%) and urban USA (32.8%)25. The high prevalence of MS in our study could be related with high prevalence of obesity, diabetes, dyslipidemia and hypertension due to changes of lifestyles and food intakes in China2627.…”
Section: Discussioncontrasting
confidence: 53%
“…In addition, differences between urban and non-urban populations in the prevalence of the MetS were observed, with this condition being more frequent in non-urban areas. The data from the 1999–2006 National Health and Nutrition Examination Survey also showed that non-urban dwelling was associated with a higher prevalence of MetS among adults in the United States [36]. This disparity, which was also found in other countries [37], may be explained by demographic and socio-economic factors [38].…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing obesity and sedentary lifestyle during the past decade [5-7], the prevalence of MS has been rising worldwide [8-10]. Although it’s well documented that the MS is highly prevalent in urban residents, some epidemiological studies suggest that the rural residents are associated with higher or comparative prevalence of MS among adults in the Unites States [11], Korea [12,13] and Thai [14]. …”
Section: Introductionmentioning
confidence: 99%